(untitled) (Bioscience Journal, 2023)
In intensive beef cattle production systems, silage, corn, soy bean, and their coproducts are commonly used as feed. However, these ingredients are highly susceptible to contamination by fungi and mycotoxins, which may lead to immunological challenges and reduce animal production. The aim of the present study was to evaluate the effects of mycotoxin contamination of diet on intake, digestibility, and performance of heifers. Twenty non-pregnant (Nellore) heifers (age, >18 months; initial body weight, 348±30 kg) were used and randomly distributed in two treatments: (1) control (non-contaminated diet) and (2) zearalenone-contaminated diet (300 ppb). The diet comprised 70% corn silage and 30% concentrate. Individual dry matter intake and digestibility were estimated using external and internal markers. Heifer body weight was evaluated every week without fasting to calculate performance. The experimental design was completely randomized. Each animal was considered one experimental unit. Assumptions were tested for variance analyses (error normality, independence of errors, and homogeneity of variances) (p<0.05). There were no differences in dry matter intake (p=0.96) and digestibility (p=0.62). Performance (kg/day) did not vary as a function of zearalenone ingestion (p=0.68). Therefore, contamination of diet with 300 ppb zearalenone did not affect the intake, digestibility, and performance of feedlot-finished heifers.